Teacher readiness in terms of the teacher attitudes towards teaching secondary school quantum physics in Sabah - Stephanie Sungkim; Mohd Zaki Ishak (Malaysia Association of Research and Education for Educators (MAsREE), 2022)
Modern technology is essentially dependent on quantum physics in today's world, and the rapid growth of technology necessitates the inclusion of Quantum Physics (QP) into a variety of fields, including industry and daily life. As a result, the inclusion of QP in the school curriculum in 2021 is expected to keep pace with the rapid advancement of technology, which will begin with the youngest kids. As a result, this study sought to ascertain the level of teacher preparedness for teaching secondary school QP in Sabah. This quantitative study used a survey design and a sample size of 175 Form Five Physics teachers in Sabah who were chosen through a multistage cluster sampling procedure. The research tool was a questionnaire that had been adapted and modified. The instrument's reliability was high, at .87. The study's data were analysed using IBM SPSS version 28.0 software. The study's findings indicate that teacher readiness is high in terms of teacher attitudes (m=7.91). The outcomes of this study can help policymakers and the Malaysian Ministry of Education gain a better understanding of the current status of Physics teachers' perceptions toward QP implementation once it has been implemented in 2021. The study's results also indicate that teacher attitudes toward teacher readiness are critical for maintaining the quality of secondary school QP teaching.